2011
DOI: 10.1021/es200702m
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Palladium Enhances Diatrizoate Removal from Hospital Wastewater in a Microbial Electrolysis Cell

Abstract: To decrease the load of pharmaceuticals to the environment, decentralized wastewater treatment has been proposed for important pointsources such as hospitals. In this study, a microbial electrolysis cell (MEC) was used for the dehalogenation of the iodinated X-ray contrast medium diatrizoate. The presence of biogenic palladium nanoparticles (bio-Pd) in the cathode significantly enhanced diatrizoate removal by direct electrochemical reduction and by reductive catalysis using the H 2 gas produced at the cathode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Studies showing the residence of polycyclic aromatic hydrocarbons, hormones, prescription and over the counter drugs, and other medical wastes have led to many alternative approaches to treatment. Iodinated X‐ray contrast media such as diatrizoate and iohexol represent unique challenges to waste management systems . These compounds are administered to patients in very high dosages (therapeutic levels are near molar concentrations), are not metabolized by the body and are therefore excreted, largely unmodified, into the waste water stream .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showing the residence of polycyclic aromatic hydrocarbons, hormones, prescription and over the counter drugs, and other medical wastes have led to many alternative approaches to treatment. Iodinated X‐ray contrast media such as diatrizoate and iohexol represent unique challenges to waste management systems . These compounds are administered to patients in very high dosages (therapeutic levels are near molar concentrations), are not metabolized by the body and are therefore excreted, largely unmodified, into the waste water stream .…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are administered to patients in very high dosages (therapeutic levels are near molar concentrations), are not metabolized by the body and are therefore excreted, largely unmodified, into the waste water stream . As a result, waste management systems near medical facilities are often faced with large spikes in the concentrations of these compounds …”
Section: Introductionmentioning
confidence: 99%
“…20 Pd(0) particles have been reported frequently as the catalyst of the reduction of halides, such as trichloroethylene (TCE), chlorophenols and diatrizoate. [21][22][23][24] This study chose diatrizoate as the halide to test the catalytic activity of Pd(0) particles in extreme thermophilic condition. As shown in Fig.…”
Section: Enhanced Decolorization and Dehalogenationmentioning
confidence: 99%
“…the cathode can be employed to produce H 2 in a sustainable way to provide an economical interesting reactant for bio-Pd catalyzed dehalogenation reactions. It is of great interest to examine the impact of decorated electrode on the performance of contaminants removal such as diatrizoate degradation and chlorinate hydrocarbons reduction (Hosseinkhani et al, 2013;De Gusseme et al, 2011;Hennebel et al, 2011). Studies have demonstrated that bioPd decorated electrode enhanced the efficiency of contaminants removal (Hosseinkhani et al, 2013;De Gusseme et al, 2011;Hennebel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is of great interest to examine the impact of decorated electrode on the performance of contaminants removal such as diatrizoate degradation and chlorinate hydrocarbons reduction (Hosseinkhani et al, 2013;De Gusseme et al, 2011;Hennebel et al, 2011). Studies have demonstrated that bioPd decorated electrode enhanced the efficiency of contaminants removal (Hosseinkhani et al, 2013;De Gusseme et al, 2011;Hennebel et al, 2011). However, this kind of Pd-cell have rarely been used as electrocatalyst directly because of the poor conductive nature of microbial cells Xiong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%